TECHNOLOGY-ENHANCED TECHNIQUES FOR LEARNING MATHEMATICS: A BIBLIOMETRIC PERSPECTIVE - Abu, Zunainah; Abdollah, Badariah; Mohd Zaki, Nurul Izzati (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2025)
The rapid incorporation of digital tools and emerging technologies has transformed mathematics education, prompting scholars to investigate technology-enhanced techniques that can improve teaching and learning effectiveness. Nonetheless, despite the growing body of research, there exists a need to systematically examine publication trends, influential works, and collaborative patterns in this field to better understand its evolution and future direction. This research bridges this gap via a bibliometric analysis of research on technology-enhanced learning in mathematics. Data were collected using the Scopus advanced search with specific keywords (“teaching,” “learning,” “mathematics,” “technology,” and “digital”), resulting in 1,248 relevant documents. To ensure data accuracy and consistency, OpenRefine was applied for cleaning and harmonization. The Scopus Analyzer was then used to generate descriptive statistics and graphical representations of publication trends, while VOSviewer software was employed to visualize co-authorship networks, country collaborations, citation patterns, as well as keyword co-occurrence maps. The findings demonstrate a steady increment in publication output from 2015 to 2025, with notable peaks during the COVID-19 pandemic years, reflecting the urgent demand for digital and remote learning solutions. The United States, Indonesia, China, and Malaysia emerged as the most active contributors, while highly cited articles focused on themes of equity in STEM, digital learning innovations, and project-based learning approaches. Keyword mapping highlighted clusters around “mathematics education,” “e-learning,” “educational technology,” and “STEM integration,” underscoring the interdisciplinary nature of the field. This research contributes to the body of knowledge by providing a comprehensive overview of research trends and global collaborations, offering insights for educators, policymakers, and researchers seeking to advance technology-enhanced mathematics education.